The Yellow House - Oppenheim, Edward Phillips (Saga Egmont, 2021)
Also published under the title ‘As a Man Lives’, ‘The Yellow House’ is an E. Phillips Oppenheim tale packed full of his trademark mystery and suspense. The story is narrated by our protagonist Kate Ffolliott, who has recently returned to England following completion of her studies in Germany. Beautiful and popular, Kate soon finds herself the centre of attention. Romance, passion, and jealousy ensue in this gripping story full of unexpected twists and turns.